Pengaruh Literasi Keuangan, Persepsi Resiko, dan Persepsi Imbal Hasil terhadap Minat Investasi Sukuk Tabungan di KPP Mataram Barat - Primananda, Presta Ditya; Salahuddin, Muh.; Syawahid, M. (AS-SABIQUN, 2025)
Investment is a commitment to a certain amount of funds or other resources that are made now, with the aim of gaining profit in the future. Investment can also be said as a delay in the use of consumer goods for productive things in a certain period of time. The Self Assessment System is a tax collection system where taxpayers are given the trust to calculate, calculate the taxes owed themselves and then pay them off and report them to the Tax Service Office where the taxpayer is registered. The purpose of this study was to examine the effect of Self Assessment System, tax audit, and tax law enforcement of Islamic Banks on tax revenue at the West Mataram Pratama Tax Service Office. This study used a saturated sampling technique by selecting 97 employee samples at the West Mataram Pratama Tax Service Office. This study used primary data from questionnaires filled out via Google Form and assessed using a Likert scale. The data analysis technique used in this study used multiple linear regression model analysis with the help of the International Business Machines Statistical Package for the Social Sciences 25 program. The results of the study showed that partially the significance value of the Self Assessment System (0.815>0.05) and tax audit (0.224>0.05) did not have a significant effect on tax revenue at the West Mataram Pratama Tax Service Office. While the significance value of tax law enforcement of 0.000 is smaller than 0.05, which means that tax law enforcement has a significant effect on tax revenue at the West Mataram Pratama Tax Service Office. Simultaneously, the significance value of the Self Assessment System, tax audits, and tax law enforcement show a positive and significant influence on tax revenue at the West Mataram Pratama Tax Service Office with a significance value of less than 0.05 (0.000<0.005).